Intervertebral Movements and Changes in Intervertebral Foraminal Morphology in the Lumbar Spine During a Chiropractic Procedure: A Cadaveric Study - Maruti R. Gudavalli; Gregory D. Cramer; Avinash G. Patwardhan (Mary Ann Liebert, 2023)
Objective: The objective of this study was to quantitatively determine intervertebral motions and changes in the intervertebral foramen (IVF) area, height, and width in the lumbar spine during the application of a chiropractic procedure. Methods: Eight unembalmed cadavers (five male and three female, age range 43?87 years) were procured for these experiments. Infrared light emitting markers were attached to L4, L5, and sacrum using metal rods to track the three-dimensional motion using the OPTOTRAK system. Five 4-sec cycles of flexion?distraction were performed over a 20-sec period by three clinicians. Vertebral movement data were collected using the marker data in three dimensions and the IVF by digitizing the IVF and computing the changes in area, height, and width. Vertebral motions were computed using three-dimensional kinematics in flexion, lateral bending, twisting, axial traction, and by digitizing the IVF contours; the dimensional changes in terms of height, length, and width were computed. Results: The flexion?distraction procedure created vertebral motions. Mean and standard deviation (SD) values of movements at L4?L5 were (1) 4.2? (0.78) in flexion and mean and SD values of vertebral separations were 1.10 (0.20) mm, respectively. Mean and SD values of vertebral movements at L5?S1 were 3.68? (0.69) in flexion and mean and SD values of vertebral separations were 0.80 (0.15) mm, respectively. Clinicians have created similar movements. Increases were observed in IVF dimensions in terms of area, height, and width at the L4?L5 and L5?S1. Mean and SD values of IVF changes in area, height, and width at L4?L5 were 21.12 (3.87)%, 12.13 (1.89)%, and 5.12 (1.88)%, respectively. Mean and SD values of IVF changes in area, height, and width at L5?S1 were 18.02 (2.97)%, 8.11 (1.68)%, and 4.11 (1.40)%, respectively. Conclusions: Intervertebral motions and IVF dimensional increases were noticed during the flexion?distraction procedure.